Crisis and Social Regression in Brazil A New Moment of the Social Question - Véras de Oliveira, Roberto (SpringerBriefs in Sociology, 2019)
This is the first book published in English to present a concise but panoramic overview of the social, economic and political roots of the current Brazilian crisis. By situating former president Dilma Rousseff's impeachment in the wider context of the historical struggle for social rights, citizenship and democracy in the country, the book provides a conceptual framework that will allow foreign readers to better understand the apparent contradiction of a rising regional power that all of a sudden entered in one of the worst economic, social and political crisis of its history. This book will be of interest to a wide range of social scientists (such as sociologists, economists, historians and political scientists) interested in labor and citizenship issues in developing countries like Brazil, as well as for social agents (from the public and private spheres) with practical involvement with such issues, such as trade unionists, leaders and advisors of business organizations, policy-makers, politicians, NGO activists and technicians. .